2014
DOI: 10.1186/1471-2458-14-991
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus vaccination booster does not provide additional protection in adolescents: a cross-sectional school-based study

Abstract: BackgroundCurrent consensus does not support the use of a universal booster of hepatitis B virus (HBV) vaccine because there is an anamnestic response in almost all children 15 years after universal infant HBV vaccination. We aimed to provide a booster strategy among adolescents as a result of their changes in lifestyle and sexual activity.MethodsThis study comprised a series of cross-sectional serological surveys of HBV markers in four age groups between 2004 and 2012. The seropositivity rates of hepatitis B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
6
0
4
Order By: Relevance
“…In the face of the possibility of declining titres with age irrespective of the vaccination schedule of infants 5,17 , and the loss of immune memory 8,28 , it may be important to consider 100 mIU/ml as the desired response after vaccination since the use of either one or multiple vaccines from different manufacturers significantly contributed to that level of protection.…”
Section: Discussionmentioning
confidence: 99%
“…In the face of the possibility of declining titres with age irrespective of the vaccination schedule of infants 5,17 , and the loss of immune memory 8,28 , it may be important to consider 100 mIU/ml as the desired response after vaccination since the use of either one or multiple vaccines from different manufacturers significantly contributed to that level of protection.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study in 2014, 8 we studied 38 18-year-old individuals (birth cohort 1993e1994) who had studied in our senior high school prior to attending our university. Among the 25 booster recipients, 96% (24/25) regained protective levels of anti-HBs with a median anti-HBs titer of 353 mIU/ mL after one booster dose of HBV vaccine at age 15.…”
Section: Longitudinal Studymentioning
confidence: 99%
“…A typical anamnestic response is characterised by a rapid 10-100-fold increase in specific antibodies, which starts 5-8 days after the re-exposure to the antigen and peaks after about 14 days [2][3][4]. HBsAg-specific memory has been shown to persist for at least 15-17 years after immunisation [5][6][7]. Long-term follow-up studies have shown that clinical HBV-disease or HBsAg-carrier status rarely occur among successfully vaccinated individuals, even in the case of anti-HBs titres <10 IU/l [8].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-HBs antibodies can be reliably measured by standardised tests, but no standardised method is yet available for measuring specific immune memory. In studies in which immune memory was shown by means of the increase in anti-HBs after booster vaccination, anti-HBs titres were mostly measured only once and at rather different time points, ranging from 10 days to 2 months post-booster [7,[18][19][20][21]. In addition, in some studies anamnestic response was defined as an increase in anti-HBs to ≥10 IU/l [21][22][23][24][25], in other studies as 4-fold increase in anti-HBs [5], and sometimes both criteria were applied [13,15,20,26].…”
Section: Introductionmentioning
confidence: 99%